Flow shortfall analysis in a forced-draft fan: proposals of geometrical changes for the original design - Zaleta-Aguilar, A.; Belman-Flores, J. M.; Pérez-Trujillo, J. P.; Álvarez-Vargas, L. A.; Gámez-Arredondo, S. A. (Acta Universitaria, 2016)
This paper presents fluid dynamic analysis through computational fluid dynamics (CFD) in a forced draft fan which has been modified from its original design due to its lack of volumetric flow observed during its operation. The analysis started with thermodynamic characterization of the fan, beginning from the proposed geometrical modifications like the increase of the blade size and the diameter of the rotor, achieving a flow of 8800 m3/min. Next analysis is related to influence of speed and pressure of the air flow to the fan outlet due of the increase of angular speed and potential. An angular speed of 1185 rpm and a discharge speed of 25m/s were obtained from the analysis with a total pressure of 5.44 kPa; while at the proposed angular speed, these values are closed to 30m/s and 7.5 kPa. With aim to verify that the proposed modifications do not damage the fan by vibration, a finite element analysis was developed with purpose of finding natural frequencies and vibration modes. For an operation frequency of 19.75Hz (1185 rpm), 4 natural frequencies were obtained in the analysis, in which the closest frequencies are of 18.52 Hz and 18.58 Hz, which are barely below the operation frequency. This study concluded that the proposed modifications to the geometry of the fan are adequate for its operation.